2011
DOI: 10.1111/j.1939-1676.2011.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Characteristics and Prognostic Variables of Dogs with Preclinical Chronic Degenerative Mitral Valve Disease Attributable to Myxomatous Degeneration

Abstract: Background: Preclinical myxomatous mitral valve degeneration (MMVD) includes a heterogeneous group of dogs. Therefore, identifying risk factors for progression of the disease is of clinical importance.Objectives: To investigate survival time and risk factors for clinical and echocardiographic variables taken at initial examination for clinical progression in preclinical MMVD dogs.Animals: A total of 256 dogs with stage B1 or B2 MMVD. Materials and Methods: Medical records of 256 dogs with preclinical MMVD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 41 publications
(64 reference statements)
10
116
1
8
Order By: Relevance
“…3,46 In a meta-analysis of 256 dogs with MMVD, 42 heart rate was not among the variables associated with a progression of heart failure class or survival. In cross-sectional studies, heart rate variability 47 and mean heart rate 48 changed with progression of MR, but heart rate itself and increase in heart rate, as a predictors of CHF, have to date not been evaluated in longitudinal models (Fig.…”
Section: Heart Ratementioning
confidence: 95%
See 2 more Smart Citations
“…3,46 In a meta-analysis of 256 dogs with MMVD, 42 heart rate was not among the variables associated with a progression of heart failure class or survival. In cross-sectional studies, heart rate variability 47 and mean heart rate 48 changed with progression of MR, but heart rate itself and increase in heart rate, as a predictors of CHF, have to date not been evaluated in longitudinal models (Fig.…”
Section: Heart Ratementioning
confidence: 95%
“…These findings are in concordance with earlier reports. 30,42,45 Although both predictors were significant as baseline variables in the Cox model, the baseline analysis is biased because one study inclusion criterion was an audible heart murmur; thus, we know that these animals are at risk before inclusion. 2 …”
Section: Heart Murmurmentioning
confidence: 98%
See 1 more Smart Citation
“…The same study showed that 13% of dogs progressed to a more advanced stage of MMVD during the observation period. 54 Another recent study reported that 82% of pre-clinical dogs were still asymptomatic 12 months later. 55 Because the assessment of MMVD severity is not universally standardadized, reports on the natural history and prognosis of dogs with MMVD are somewhat variable.…”
Section: Natural Historymentioning
confidence: 99%
“…3 However, MMVD also has a variable natural history, with heterogeneity of the rate of disease progression. 7 We wished to examine whether dogs that went on to die of their heart disease would have a different rate of change of echocardiographic indices compared to a sample of dogs at various stages of their disease process. Assuming that death due to a non-cardiac disease process is just as likely to occur at any stage in the progression of mitral valve disease we could consider these dogs as representing a random cross section of dogs at various points in the progression of their valvular heart disease (albeit affected by a co-morbidity).…”
Section: Introductionmentioning
confidence: 99%